Student Practice Opportunities in Core Mathematics Instruction: Exploring for a Goldilocks Effect for Kindergartners With Mathematics Difficulties. (May 2019) - Doabler, Christian T.; Gearin, Brian; Baker, Scott K.; Stoolmiller, Mike; Kennedy, Patrick C.; Clarke, Ben; Nelson, Nancy J.; Fien, Hank; Smolkowski, Keith
Opportunities for practice play a critical role in learning complex behaviors. In the context of explicit mathematics instruction, practice facilitates systematic opportunities for students with mathematics difficulties (MD) to learn new mathematics content and apply such knowledge and skills to novel mathematics problems. This study explored whether there is an optimal amount of student practice that teachers should provide in core mathematics instruction to maximize the mathematics achievement of kindergarten students with MD, a so called "Goldilocks effect, " as opposed to simply "more is better." Results from observation data collected in a large-scale efficacy trial supported the latter rather than the former. Specifically, we found that three individual practice opportunities for every explicit teacher demonstration of mathematical content was associated with increased mathematics achievement for students with MD relative to fewer practice opportunities. Implications for facilitating frequent student practice opportunities during core mathematics instruction and designing professional development for teachers who work with students with MD are discussed.